Social and legal frameworks in publishing content on the dawn of the twenty-first century - Casas Sánchez, Ricardo; Arias Coello, Alicia (Revista General de Información y Documentación, 2016)
This article addresses the current social and legal frameworks that affect circulation and amplification of data, information and knowledge as an integral part of the process of capital accumulation, Knowledge Economy or Cognitive Capitalism; and on the other hand, conceptions framing knowledge as a free resource sharing under the headings of the theory of common property in the digital commons. The definitions of "editing", "publication" and "publishing" in the digital network environment standardized by the Internet in the XXI century as well as its necessary mapping from the perspective of Information Science are reviewed.